Negative thermoelectric power of melt mixed vapor grown carbon nanofiber polypropylene composites. (September 2019) - Paleo, A.J.; Vieira, E.M.F.; Wan, K.; Bondarchuk, O.; Cerqueira, M.F.; Goncalves, L.M.; Bilotti, E.; Alpuim, P.; Rocha, A.M.
Abstract: In this work, commercial vapor grown carbon nanofibers (CNF), produced by chemical vapor deposition (CVD), were melt extruded with polypropylene (PP) with the aim of analyzing their thermoelectric properties (i.e., electrical conductivity, thermoelectric power, power factor and figure of merit). Unexpectedly, all PP/CNF composites showed negative thermoelectric power (TEP) values instead of showing the typical positive TEP observed for this type of carbon-based polymer composites. These results can be attributed to the double layer structure surrounding the tubular core of the carbon nanofiber grown by the CVD method at 1100 °C, which may lead the intrinsically negative TEP contribution from the larger inner layer to counteract the positive TEP contribution from the smaller outer layer due to common oxygen doping. Overall, all composites showed negative TEP values around −8.5 μVK −1 and a maximum power factor of 1.75 × 10 -3 μW m -1 K −2, corresponding to a figure of merit of 1.2 × 10 -6 at room temperature. This study demonstrates that melt mixed polymer composites with large-diameter tubular carbon nanostructures and negative Seebeck coefficients can be directly produced with large-scale processing methods without requiring specific additives and/or deoxygenation treatments. Graphical abstract: Electrical conductivity (solid symbols), power law fitting, and negative Seebeck coefficient (open symbols) as function of CNF content in PP/CNF composites.Image 10095